The Model of Container Feeder Line Organization Focused on the Nature and Parameters of External Container Flows - Oleksii Drozhzhyn; Yuliia Koskina (Communications - Scientific letters of the University of Zilina, 2021)
This article considers the trunk lines, connected with the feeder region as the external environment for the system - feeder lines (its subsystems are container flows, ports and container ships). Hub ports are considered to be the boundary of the system and the external environment. Thus, mathematical models were simulated for the two levels. At the first level, container flows are determined (based on statistical data), which enter and exit the hub. At the second level, the mathematical model allows to find for the feeder line: volumes of container flows, the total capacity of the ships which serves the cargo, and parts of the distribution of this capacity between feeder ports.